Workshop Perangkat Pembelajaran PjBL Berbasis Deep Learning - Winda Agustina; Rahmita Yuliana Gazali; Abdul Jabar; Aminah Ekawati; Dina Huriaty; Muhammad Royani; Benny Nawa Trisna; Arifin Riadi (Abdimas Mandalika, 2026)
Abstract:  21st-century mathematics education demands the application of approaches that can develop conceptual understanding, critical thinking skills, creativity, and student collaboration. One of the relevant approaches is deep learning, but its implementation in schools still faces various challenges, especially the limited understanding of teachers in selecting learning models and developing appropriate teaching materials. This community service activity aims to facilitate MTs Tabalong teachers and teachers involved in the Mathematics MGMP throughout the city of Banjarmasin in designing and implementing Project-Based Learning (PjBL) based learning tools with a deep learning approach. The activity was conducted using a participatory training approach thru four stages: problem identification, preparation, implementation, and evaluation, with a hybrid implementation model. The participants of the activity numbered 80 teachers, consisting of 30 teachers from MTs Tabalong and 50 teachers from SMA/MA or equivalent. Data were obtained thru teacher response questionnaires and the review of teaching materials. The results show a very positive response, the material is considered relevant and beneficial, and it enhances teachers' understanding and readiness. Although the number of devices produced is not yet optimal, their quality has reflected the main characteristics of PjBL and deep learning. These findings indicate that the workshop is effective as an initial step in enhancing pedagogical competence and needs to be followed up with continuous mentoring.Abstrak: Implementasi pendekatan deep learning dalam pembelajaran matematika di sekolah masih menghadapi kendala, terutama keterbatasan guru dalam merancang perangkat pembelajaran yang sesuai. Kegiatan pengabdian kepada masyarakat ini bertujuan memfasilitasi guru MTs Tabalong dan guru yang tergabung dalam MGMP Matematika se-Kota Banjarmasin dalam merancang dan mengimplementasikan perangkat pembelajaran berbasis Project-Based Learning (PjBL) dengan pendekatan deep learning. Kegiatan dilaksanakan menggunakan pendekatan pelatihan partisipatif melalui empat tahapan, yaitu identifikasi masalah, persiapan, pelaksanaan, dan evaluasi, dengan model pelaksanaan hybrid. Peserta kegiatan berjumlah 80 guru, terdiri atas 30 guru MTs Tabalong dan 50 guru SMA/MA sederajat. Data diperoleh melalui angket respon guru dan telaah perangkat pembelajaran. Hasil menunjukkan respon sangat positif, materi dinilai relevan dan bermanfaat, serta meningkatkan pemahaman dan kesiapan guru. Meskipun jumlah perangkat yang dihasilkan belum optimal, kualitasnya telah mencerminkan karakteristik utama PjBL dan deep learning. Temuan ini menunjukkan bahwa workshop efektif sebagai langkah awal peningkatan kompetensi pedagogik dan perlu ditindaklanjuti dengan pendampingan berkelanjutan.